Redefining Green Accounting in the Health Field: A Phenomenological Study - Mir’atussholiha, Baiq Khovifa; Sokarina, Ayudia (International Journal of Business and Applied Economics, 2024)
The aim of this research is to interpret Green Accounting in the health sector based on stakeholders, namely employees and patients of the Tanjung Karang Community Health Center. This research uses a qualitative approach with phenomenology as the research method. Data collection techniques were carried out through observation, in-depth interviews and documentation. The informants in this research were the treasurer and person in charge of the environment as internal stakeholders and the community (patients) as external stakeholders who were visiting. The results of this research show that green accounting in the health sector is interpreted as compiling, recording and presenting information on infectious and non-infectious waste processing which is carried out with compliance and caution by stakeholders, thus encouraging the creation of cleanliness, comfort and admiration for the surrounding environment. Through this research, theoretical implications are produced that provide insight into the new meaning of green accounting in the health sector. Apart from that, there are also practical implications for accountants and even academics regarding green accounting analysis in the context of financial reports as well as encouraging further discussion about green accounting, especially in the health sector.